Render Forest Application to Improve A1 Level Reading Comprehension for French Department Students - Tengku, Tengku Ratna Soraya; Nurilam Harianja; Isda Pramuniati; Mahriyuni (LPPM Undiksha, 2024)
There are still many students who experience difficulties in learning languages, especially French. This research aims to analyze the application of the Render Forest application to improve A1 level students' reading comprehension. The subjects of this research were even semester students of the French Department. The method used in this research is Action Research. This research uses a Kurt Lewin design which consists of four stages, namely planning, implementation, observation and reflection. Data collection methods use observation, questionnaires and tests. The instruments used to collect data were questionnaire sheets and test questions. The subjects involved were 36 students. The data analysis techniques used are qualitative and quantitative data. This research found that using the Render Forest application improved A1 level students' reading comprehension in various ways. First, students are interested in the Render Forest application as an application for reading text. Second, Render Forest is an application that is familiar to students. Students feel comfortable and easy to adapt to this application. Additionally, quantitative data supports these findings, indicating that students have made some progress. The student's pre-test score at the beginning was 44.34. After cycle I was completed, it increased to 73. After cycle II, students finally achieved the research goal, namely 85. In conclusion, the Render Forest application improved students' reading comprehension at Level A1.